Seasonality in feed availability and nutritional status of goats in heavy rainfall region of south Gujarat - SORATHIYA, L M; FULSOUNDAR, A B; TYAGI, K K; PATEL, M D (The Indian Journal of Animal Sciences, 2016)
The seasonality pattern in availability of grazing and browsing along with nutritional status of grazing goats in heavy rainfall region of south Gujarat were studied for a year by monitoring 360 goats from 8 villages. The nutritional status of experimental goats was judged by body condition scoring (BCS), FAMACHA (FAffa MAlan CHArt) and by analyzing packed cell volume (PCV). The availability of grazing and browsing resources was judged by participatory rural appraisal tools. The collected data wasfrequencised, tabulated and analyzed by various suitable techniques in IBM® SPSS® Statistics Version 20.0. The study revealed that a period from September to December was flush and May- August was lean period as far as availability of grazing or browsing resources. The grass is found in plenty in monsoon months; however, due to kharif crops most of the ways and roads are not accessible for goats. The BCS was highest (3.13±0.04) in winter and lowest in monsoon (2.74±0.03). The majority (57.5%) of goats was having low BCS in monsoon and good BCS in other seasons. The FAMACHA score was high in monsoon where as it was at par in winter and summer season. Frequency distribution of experimental goats based on FAMACHA score range shows that in monsoon, 40.8% and 15.8% goats were having either borderline or severe score. The PCV was significantly low (20.47±0.43) in monsoon. Overall 31.67% of goats were having low PCV indicating that they were more or less anaemic during whole year. The BCS were negatively correlated with FAMACHA and positively correlated with PCV. It can be concluded that the feed availability and nutritional status of grazing goats in south Gujarat is poor during monsoon months.